Perceived barriers to entry: are there any differences between small, medium-sized and large companies?. (31st July 2006) - Kemp, Ron; Lutz, Clemens
The objective of this paper is to provide empirical evidence about the importance of barriers to entry. In particular, the perceptions of firms are considered. Three questions are addressed: which entry-barriers are important in the perception of firms in the Dutch economy? Do these perceptions differ between sectors? Do these perceptions differ between small and large firms? It is shown that the procurement of a viable sales volume, access to capital and financial risk, are considered to be the major barriers. The ranking of the importance of specific barriers to entry coheres among the sectors under study. The most remarkable result is that the figures indicate that micro firms perceive lower barriers to entry than medium-sized and large firms.